Asian development outlook (ADO) 2019 supplement growth slows further in developing Asia’s giants. - Asian Development Bank (Mandaluyong City, Metro Manila Asian Development Bank, 2019)
Excluding newly industrialized economies, regional growth forecasts are revised down to 5.7% for both 2019 and 2020. Regional inflation projections are revised up to 2.8% for 2019 and 3.1% for 2020 as African swine fever continues to elevate pork prices. Elusive trade conflict resolution weighs on sentiment and activity in the region, with further delay still the foremost downside risk to the forecasts.
Keywords: Economics; Industry and state